Reliability of typical radiographic features in Bosworth fracture-dislocations - Bartoníček, Jan; Rammelt, Stefan; Tuček, Michal; Kostlivý, Karel; Malík, Jozef; Stöckigt, Caroline (European journal of trauma and emergency surgery, 2025)
PURPOSE: Bosworth fracture-dislocations (BF) with entrapment of a fibular fragment behind the posterior rim of the distal tibia are rare but potentially serious injuries to the ankle. MATERIALS AND METHODS: We analyzed the radiographs of 23 consecutive patients with a mean age of 44 years who were treated for BF. All patients underwent routine radiological examination of the ankle and presence of a BF was confirmed intraoperatively in 22 cases and / or with CT in 15 cases. RESULTS: Tibiofibular overlap intersecting the joint line in the anteroposterior view of the ankle was found in 20 of 23 cases (87%) and persisted in 17 of 18 cases (94%) after unsuccessful closed reduction. Posterior subluxation of the talus in the lateral view was revealed in 21 of 23 cases (91%). Tibio-fibular dissociation, i.e., posterior displacement of the distal fibula relative to the distal tibia in the lateral view was found in 22 of 23 cases (96%). This sign remained positive in all 18 cases with unsuccessful closed reduction. Closed reduction of the talus beneath the distal tibia was associated with an average increase of anterior fibular angulation of 24.5 degrees in case of inadequate closed reduction. CONCLUSIONS: Bosworth fracture represents a rare but still highly variable ankle injury that may lead to misinterpretation of the initial radiographs. Reliable radiological signs are triangular tibiofibular overlap, posterior talar subluxation and tibiofibular dissociation that should prompt CT imaging which is essential for revealing the complex pathoanatomy and planning the surgical approach.
Keywords: Young Adult; Male; poranění kotníku; počítačová rentgenová tomografie; retrospektivní studie; Fracture Fixation, Internal; vnitřní fixace fraktury; mladý dospělý; fraktury kotníku; Adolescent; CT diagnostics; fibula; radiografie; Adult; Aged; dospělí; fraktury tibie; mužské pohlaví; senioři; reprodukovatelnost výsledků; Reproducibility of Results; mladiství; Tomography, X-Ray Computed; Fracture Dislocation; Fibula; lidé; ženské pohlaví; Ankle fracture-dislocations; Humans; Tibial Fractures; Ankle Fractures; Bosworth fracture; Ankle Injuries; dislokovaná fraktura; Retrospective Studies; Female; Posterior malleolus; lidé středního věku; Radiography; Middle Aged